Upaya Peningkatan Kemampuan Penggunaan Microsoft Access Programming Bagi Pegawai Unit Usaha Bank Sumut Syariah - Dian Noviandri; Indra Hermawan; Agnita Yolanda; Fahmi Sulaiman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This training aims to improve the ability to use microsoft access programming for employees of the Bank Sumut Syariah business unit. This training was attended by all employees because this training is considered very important to support the performance of the employees. Currently, the Bank Sumut Syariah business unit has implemented technology based on Microsoft Access Programming in the context of carrying out all office activities. This training is carried out by means of socialization to employees, discussions, training and also direct practice of its use. The service activities for the Microsoft Access Programming Training have been carried out well. The service activity for the Microsoft Access Programming Training received an enthusiastic response from the participants of the Bank Sumut Syariah unit employees. Microsoft Access Programming training is carried out in stages and distributed in 14 meetings with a student center learning system and project based learning model so that employees can solve work problems with the skills that have been taught. Microsoft Access is a relational computer database application program that is used to design, create and process various types of data with large capacities. Database is a collection of related tables. Between tables with one another are related to each other, so it is often called a relational database. The relations between tables are connected by a key, namely the primary key and foreign key